The Effect of Emotional Dysregulation, Loneliness and Self-Compassion on Nonsuicidal Self-Injury Behavior on Overseas Students - Askina, Meutia; Selviana, Selviana; Sovitriana, Rilla (Dinasti Health and Pharmacy Science, 2024)
News about the phenomenon of self-harm or nonsuicidal self-injury has been rampant in recent years. Nonsuicidal self-injury is a behavior that is often done to overcome negative or difficult feelings. Nonsuicidal self-injury is influenced by several factors including emotional dysregulation, loneliness and self-compassion. This study aims to determine whether there is an influence of loneliness and self-compassion on nonsuicidal self-injury behavior on overseas students in Java and Sumatra. The measuring instruments used are the Indonesian version of the Self-Harm Inventory (SHI), Difficulties with Emotion Regulation Scale (DERS16), De Jong Gierverld Loneliness Scale (DJGLS), Self-Compassion Scale Short Form (SCSSF), with analysis using JASP 0.18.3.0 for windows. The results shows that there is a significant influence between emotional dysregulation, loneliness and self-compassion on nonsuicidal self-injury behavior on overseas students in Java and Sumatra. These findings provide scientific evidence that emotional dysregulation, loneliness and self-compassion can be important factors influencing nonsuicidal self-injury behavior.